ORGANIZATIONAL AND LEGAL MECHANISMS FOR COMBATING CORRUPTION (International journal of artificial intelligence, 2026)
This article provides a comprehensive analysis of the organizational and legal mechanisms for combating corruption in the Republic of Uzbekistan. It examines scientific and legal approaches to the concept of corruption, offers a systematic classification of anti-corruption actors, and critically evaluates their powers. The author substantiates that the principles of horizontal and vertical relations within the existing institutional framework have not been fully developed, highlights the necessity of integrating financial control bodies into the system, and emphasizes the need to expand civil society participation. A comparative analysis is conducted based on the experiences of foreign countries—Singapore, the Republic of Korea, Lithuania, and Moldova.